Biliary peritonitis - Valls, Alberto; Balboa, Oscar; Asiner, Boris (Cirugía del Uruguay, 2021)
The authors define peritonitis originating in the hepatobiliary-pancreatic aparatus and characte-rized by hile in the peritoneum, as biliary peritonitis. They made the following dassification: 1) In the accessory biliary tract: a) by permeation or precocious perforation in case of an obstruction of the excretion route of the gall bladder; b) due to fall of the obstructing gallstone. 2) Of the main biliary tract, pan creas and liver: a) with gall bladder functioning due to filtration or permeation of the gall bladder; b) without a functioni'ng gall bladder (cholecystectomized, cr scleroatrophic gall bladder). These peritonitis are classified according to the location of the obstacle: at the level of the middle part of the gall bladder; in the ampulla of Vater, with a common biliopancreatic route or obstacle of the gall bladder. Pancreatitis lesion_s . Possibility of gall bladder or pancreatic lesions. Each one has a different prognosis and treatment. Thes ones that have the best prognosis are those located in the gallbladder.